Anti-Radicalism Mosque: Preaching in Jember Regency - Supriyanto Supriyanto; Sofyan Hadi; Minan Jauhari (Syntax Corporation Indonesia, 2023)
The radicalism that has started to develop in Jember Regency has received a unique response from the Government, as it is considered to have the potential to threaten the unity of the country and disrupt the democratic process, which has its own specific response. Therefore, the Government is striving to find preventive solutions to minimize such understanding. In addition, the mosques in Jember provide a moderate religious understanding so that worshippers are not influenced by extremist religious ideologies. This article aims to provide an understanding to the public that mosques are at the forefront in anticipating the entry of radical ideologies.